France’s Violations of Civilian Rights During Its Nuclear Tests in Algeria (1960–1966) - Toumi, Hamdoun (Journal of Ecohumanism, 2026)
This study examines France’s violations of civilian rights during its nuclear tests in Algeria between 1960 and 1966. International humanitarian law provides legal protection for civilians, combatants no longer participating in hostilities, and prisoners of war. These protections, established in the Geneva Conventions of 1949 and their Additional Protocols of 1977, obligate parties to armed conflicts to preserve life, dignity, and physical integrity, and prohibit inhumane treatment, collective punishment, and attacks on civilians. During the French colonial occupation, nuclear tests conducted in the Algerian desert systematically endangered civilian populations, causing immediate deaths, long-term health effects, and environmental contamination. The research demonstrates that French authorities deliberately exposed Algerian and foreign civilians to lethal radiation without precaution, in violation of international humanitarian law and human rights treaties. The study is structured into two sections: the first analyzes the protective legal framework for civilians in wartime; the second examines the specific crimes committed during France’s nuclear tests, including intentional killings, inhumane treatment, and threats of extermination. The findings reveal that these acts constitute serious violations of international law and may incur both civil and criminal accountability for the French state and responsible officials. This research underscores the importance of legal enforcement and historical recognition of civilian protection in armed and colonial contexts.